Antidiabetic and Antioxidant Activities of the Twigs of Andrograhis paniculata on Streptozotocin-Induced Diabetic Male Rats - Olubanke O. Ogunlana; Babatunde O. Adetuyi; Elohor F. Esalomi; Miracle I. Rotimi; Jacob O. Popoola; Oluseyi E. Ogunlana; Oluwatosin A. Adetuyi (MDPI AG, 2021)
Background: Diabetes is associated with chronic hyperglycaemia, long-term damage, dysfunction, and organ failure. This study aims to evaluate the antidiabetic activity of the twigs of Andrographis paniculata and its toxicological markers on Streptozotocin (STZ)-induced diabetic Albino rats. Methods: A total of thirty rats were randomly divided into five groups of six animals each. Non-diabetic animals were treated with distilled water as non-diabetic sham control group 1, while diabetic animals (group 2, 3, 4 and 5) were treated with 60 mg/kg bw STZ intravenous (iv) and 100 mg/kg body weight (bwt) of metformin orally for group 2, distilled water for group 3, and 250 and 500 mg/kg bwt of Andrograhis paniculata (A. paniculata) for groups 4 and 5, respectively. The animals were dosed for 28 days, after which they were sacrificed. Liver and kidney function tests as well as livid profile tests were used as the biomarkers of toxicological assessment. Fasting blood glucose was carried out weekly. Oral Glucose Tolerance Test (OGTT) was conducted on the 28th day of the antidiabetic assessment. Results: A. paniculata groups 4 and 5 were significant at different doses (p < 0.05) in reducing the blood glucose level in comparison with metformin. There were significant changes in total and direct bilirubin, total protein, potassium, triglyceride and inorganic phosphorus in 500 mg/kg bwt of the treated group in comparison with the metformin and diabetic group groups. A. paniculata at 500 mg/kg bwt is most effective for its antidiabetic and organ protecting effects.